Contributions to the knowledge of Ceratitis capitata Wied. (Diptera, Tephritidae) in Northern Italy I. Observations on the biology (Bollettino di zoologia agraria e bachicoltura, 2024)
Rearings carried out in Lombardy (Northern Italy) under variable conditions on different fruits and starting from wild populations have given the opportunity to ascertain some aspects of the biology of the Medfly in this region. The Medfly is active until the beginning of December, it can lay eggs until mid October, but only eggs laid no later than mid September permit the completion of the developmental cycle. The pre-imaginal development does not only depend on temperature but also on the host fruit. The development requires on average from 3 to 6 (8) weeks on peaches, and between 5 and 9 weeks on apples. The egg and larval stages are completed in 9-57 days, the pupal stage in 9-42 days, without any differences between the sexes. The sex ratio was very close to 1:1 and the average adults longevity was extremely variable, about 2.5 months in 2001 and 1-2 months in 2003, but with peaks of almost 150 days. One generation requires 1-2.5 months or more. On the basis of these data we can calculate that in one year in Lombardy there are 3-4 generations according to the climatic conditions, and that the fourth is completed only by a small number of precocious specimens, even in the most favourable years for the Tephritidae.
Keywords: Medfly; Northern Italy; wild population; developmental duration; rearing under variable condition